Anticoagulant Management of Mechanical Heart Valve Patients During Perioperative Surgery: A Case Report - Trisulo Wasyanto; Yoga Yudhistira; Nutria Anggraini; Ahmad Yasa; Irnizarifka Irnizarifka (Indonesian Journal of Medicine, 2023)
Background: Patients with mechanical heart valves require lifelong oral anticoagulation. It will be a dilemma if a patient with a mechanical heart valve has surgery. This case report aims to discuss how to interrupt oral anticoagulants and bridging therapy in patients with mechanical heart valves who will be undergoing non-cardiac surgery. Case Report: A 26-year-old pregnant woman, G1P0A0, aterm with a mechanical mitral valve, will have elective Sectio Caesarian Transperitonealis (SCTP) surgery and Intra Uterine Device (IUD) insertion. The patient had a history of mitral valve replacement surgery (MVR) in 2014 and was routinely treated with 4 mg of warfarin at night. From the examination, blood pressure was 120/80 mmHg, heart rate was 90 beats per minute, and pulse rate was 90 beats per minute. The ECG examination found sinus rhythm with 1st-degree atrioventricular block, right axis deviation, 90 beats per minute, and left atrial enlargement. We decided to have oral anticoagulant interruption and bridging therapy by stopping warfarin three days before surgery. When the international normalized ratio (INR) falls <2, patients are given heparin injections (UFH) with an APTT target of 1.5-2.0 times from basic APTT. When the patient was about to be operated on, UFH was stopped 6 hours before surgery and resumed 12 hours after surgery. Warfarin was given one day postoperatively. Patients were adjusted to the dose of UFH according to the target. This patient had no thromboembolic events or bleeding before, during, or after surgery. The patient was allowed to be an outpatient and was given home therapy with Warfarin 5 mg at night. Results: We report a case of a 26-year-old female patient with a mechanical mitral valve who was going to undergo elective SCTP surgery and an IUD insertion. Patients at high risk of thrombo¬embolism due to surgery with a high risk of bleeding. Bridging therapy was performed using UFH. In the perioperative period, the patient did not experience thromboembolic events, and bleeding before, during, and after surgery could be well controlled. Conclusion: Perioperative management of patients with mechanical heart valves must be done carefully. Interruption of oral anticoagulants should be carefully considered considering the risk of thromboembolism and bleeding during the perioperative period. Guidelines recommend that in patients with mechanical heart valves, anticoagulation interruption for minor surgeries is avoided. Whereas in patients with major surgery, it is necessary to do bridging therapy with fast-acting anticoagulants such as UFH or LMWH. Keywords: mechanical heart valve, anticoagulant interruption, perioperative, bridging therapy Correspondence: Trisulo Wasyanto. Department of Cardiology and Vascular Medicine, Faculty of Medicine, Sebelas Maret University / Dr. Moewardi Hospital. Jl. Kol. Sutarto 132, Surakarta 57126, Central Java, Indonesia. Email: trisulo.wasyanto@staff.uns.ac.id. ORCID ID: 0000-0001-9900-0497. Mobile: +62811294225.